Remoção de matéria orgânica e calibração de um modelo de remoção de amônia em uma série de lagoas de estabilização em escala real - Almeida, Anderson Ruan Gomes de (2017)
Stabilization ponds are very widespread treatment systems in Brazil due to their low cost of implementation, operation and maintenance. This treatment system has ability to remove organic matter and ammonia by biological means through relationships between bacterial and algal biomass. It is common for ponds with presence of algal biomass to present an increase in organic concentration due to the death and predation of themselves. The estimate of the algal concentration is given in terms of chlorophyll a. The characterization of the organic matter in domestic effluents is done through parameters of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). As an alternative way of evaluating the organic load generated by algae, it was proposed the use of Consumed Oxygen (OC) analysis that measures the organic portion of greater ease of biodegradation, called the labile fraction. In relation to ammonia removal, the authors Pano and Middlebrooks (1982) and Soares et al. (1996) proposed a model of total ammonia removal (AMT) in facultative ponds. The model considers that ammoniacal removal is influenced by physical, chemical and operational parameters. It was intended to evaluate the models suggested in stabilization ponds located in the ETE Tabapuá (3 ° 44'S, 38 ° 36'O), located in Fortaleza, capital of Ceará. These ponds are formed in series, consisting of a primary facultative pond (LFP) followed by a primary maturation pond (LMP) and this one by a secondary maturation pond (LMS). The pond system showed 75% BOD removal, COD of 82% and OC of 23%. In relation to the algal biomass, the LFP presented the highest chlorophyll a value (689 μg / l), coinciding with the series that showed an increase in the particulate organic concentration. OC analyzes presented satisfactory results in the evaluation of the particulate fraction of the ponds, suggesting that the increase in concentration occurs due to the excess of algal biomass. In addition, analyzes of OC suggest that the algal composition is composed mainly of labile organic carbon, having an effect on the decomposition process of both heterotrophic bacterial biomass and temperature variation. The models of ammonia removal were very relevant when analyzed in the facultative ponds (R² = 0.88, mean error = 22.0%), and the same behavior did not occur in the maturation ponds (R² = 0.47; , 5%). As a result, it was suggested the calibration of the models used as a way to meet both facultative and maturation ponds. The model presented better correlations (R² = 0.94, E = 19.9%) when compared to the proposed models, being suggested its use in systems of stabilization ponds in the state of Ceará and Northeast Region.